(untitled) (Journal of the College of Basic Education, 2022)
Two hundred and twenty clinical specimens were collected from were collected from patients in Medical City Hospitals (Baghdad /Iraq).During the period From November 2013 to April 2014.The specimens were included (54) ear swab, (56) blood, (70) burn swab, and (40) urine sample. It was found that (49.03%) of the 108 isolates were belong to Staphylococcus spp., were diagnosed as coagulase-positive staphylococci (COPS), where 112 (50.9%) of clinical samples were coagulase negative (CONS). From the collected clinical samples, 85(78.7%) were MRSA according to sensitivity test and vitek system, and the rest were MSSA 23(21.9%). In the present study, ceftaroline is drug of choice, because of it activity against Methicillin-resistant S. aureus .The effectiveness of the ceftaroline antibiotic are being tested on 85 isolate of Methicillin-resistant S. aureus (MRSA), all isolate were sensitive to ceftaroline.